2015
DOI: 10.1007/s10854-015-3316-5
|View full text |Cite
|
Sign up to set email alerts
|

Photo-catalyst tin dioxide: synthesis and characterization different morphologies of SnO2 nanostructures and nanocomposites

Abstract: In this work various morphologies of tin dioxide nanostructures were synthesized via chemical reaction between tin chloride and different capping agents. The effect of different parameters such as precursors and temperature on the morphology of SnO 2 nanostructures was investigated. Photo-catalytic property of tin oxide was examined by degradation of methyl orange as organic pollutant in water under UV light irradiation. Nanostructures were characterized by X-ray diffraction, photo luminescence, Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 44 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Considering the mentioned results, the best degradation efficiency of the prepared nanocomposite is for Methyl Orange dye which has been degraded about 94 % after 60 min and it was completely depredated after 65 min and after that, Acid brown 14 with complete degradation after about 80 min gave a satisfactory result. Organic dyes decompose to carbon dioxide, water and other less toxic or nontoxic residuals [6]. Figure 9c, d show complete degradation of the Acid brown 14 and Methyl orange dyes after 80 and 60 min exposure to the nanocomposite.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering the mentioned results, the best degradation efficiency of the prepared nanocomposite is for Methyl Orange dye which has been degraded about 94 % after 60 min and it was completely depredated after 65 min and after that, Acid brown 14 with complete degradation after about 80 min gave a satisfactory result. Organic dyes decompose to carbon dioxide, water and other less toxic or nontoxic residuals [6]. Figure 9c, d show complete degradation of the Acid brown 14 and Methyl orange dyes after 80 and 60 min exposure to the nanocomposite.…”
Section: Resultsmentioning
confidence: 96%
“…In these processes, organic molecules mainly undergo decomposition reaction by interacting with both UV (or visible) light and a photo-catalyst material to give CO 2 and H 2 O as final products [1]. One of the most appealing materials for this purpose is semiconductor nanomaterials such as TiO 2 (effective and most frequently mentioned) ZrO 2 , WO 3 , ZnO, ZnS, SnO 2 , Fe 2 O 3 , as well as large number of binary, ternary, and quaternary mixed oxides [2][3][4][5][6]. Among the mentioned materials, ZnO nanoparticles with wide band gap, high quantum efficiency, and nontoxicity exhibit significant photocatalytic activity for the decomposition of organic contaminants [7].…”
Section: Introductionmentioning
confidence: 99%
“…CdS is susceptible to producing photo-corrosion when the photo-catalytic, it is found that the synergic effects of CdS and ferrites can reduce the recombination probability of photo-generated electron-hole pairs and enhance the charge separation efficiency, leading to the higher photocatalytic performance and remarkable inhibited photocorrosion. Ferrite nanoparticles themselves have a strong magnetic property, which can be easily used for magnetic separation after degradation [19][20][21][22][23][24][25][26][27]. The present study describes the synthesis and characterization of nanosized cobalt hexaferrite particles using precipitation method.…”
Section: Introductionmentioning
confidence: 98%
“…23. Organic dyes decompose to carbon dioxide, water and less toxic or nontoxic residuals[21][22][23][24][25].…”
mentioning
confidence: 99%
“…Herein, we report a simple and surfactant-free route for the synthesis of copper pyrovanadate nanostructures via the chemical precipitation method from 3:2 molar ratio of copper-organic complexes and NH 4 VO 3 . Polymeric nanocomposites have recently gained much attention because adding a small amount of nanostructure to a polymeric matrix can lead to improvement properties of the matrix26272829. The principal profits of these compounds over many metallic alloys are corrosion resistance, low density and thermal insulation.…”
mentioning
confidence: 99%